Record-Keeping as a Factor Related to Meeting the Personal Financial Ratios Guideline - Xarba, Belinda; Bejko, Alketa; Peta, Etleva (European Journal of Economics and Business Studies, 2015)
An effective way through which the families can measure the progress of their financial situation is using personal financial analysis. The aim of this study is to determine that household record-keeping of the personal expenditures and incomes is positively significant in achieving the recommended level of liquidity ratio, saving ratio and capital accumulation ratio. This study was conducted in the region of Gjirokastra, South Albania and this paper presents the partial results of this study. The analysis of personal financial ratios applied for Albania is still a “fragile seedling”. As a result, researchers, policy-makers and groups of interest should pay more attention to it. Up to the present day, there is no recommended level for financial ratios of personal financial reviews discussed in any academic projects especially for Albania. In order to perform the analysis of the ratios we have been referring to the foreign researches and their guide levels, from which were selected the guide levels that we shall refer to during the study. Based on the analysis of data related to this study, as well as on the results of Chi-Square Test, it resulted that the managers of household who keep notes on the personal expenditures and incomes are more probable to become closer to the recommended levels of financial ratios. The lack of alternative data led us to questionnaires in order to collect information. After the data was collected and refined, the programs Microsoft Office Excel and Spss Ibm Statistics were used for their elaboration. Chi – square test was used for testing.